2017
DOI: 10.1016/j.bone.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone's enhancement of bones' osteogenic response to loading is affected by ageing in a dose- and time-dependent manner

Abstract: Decreased effectiveness of bones' adaptive response to mechanical loading contributes to age-related bone loss. In young mice, intermittent administration of parathyroid hormone (iPTH) at 20–80 μg/kg/day interacts synergistically with artificially applied loading to increase bone mass. Here we report investigations on the effect of different doses and duration of iPTH treatment on mice whose osteogenic response to artificial loading is impaired by age. One group of aged, 19-month-old female C57BL/6 mice was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
6
22
1
Order By: Relevance
“…As a result, local changes in tissue composition following PTH(1–34) treatment have the potential to enhance mechanotransduction indirectly by augmenting the mechanical stimuli osteocytes experience during physical activity. This is consistent with the additive effect PTH(1–34) treatment on bone adaptation during in-vivo loading or treadmill exercise [5052]. However, the additive effect provided by PTH(1–34) treatment is readily considered a function of PTH altering the cellular response to mechanical stimuli as well as its down-stream activation of similar anabolic mechanisms [53, 54].…”
Section: Discussionsupporting
confidence: 64%
“…As a result, local changes in tissue composition following PTH(1–34) treatment have the potential to enhance mechanotransduction indirectly by augmenting the mechanical stimuli osteocytes experience during physical activity. This is consistent with the additive effect PTH(1–34) treatment on bone adaptation during in-vivo loading or treadmill exercise [5052]. However, the additive effect provided by PTH(1–34) treatment is readily considered a function of PTH altering the cellular response to mechanical stimuli as well as its down-stream activation of similar anabolic mechanisms [53, 54].…”
Section: Discussionsupporting
confidence: 64%
“…Meakin et al (2017) reported accrual of the cortical bone in response to intermittent PTH treatment (iPTH), which additionally generated positive loadrelated osteogenic interactions in young mice. Aged mice, in contrast, exhibited no positive load-iPTH interaction in the cortical compartment [88] suggesting that aged bones have reduced sensitivity to pharmacotherapy and mechanical loading. With view to better ascertain the role of osteoclasts in aged bones, Naruse et al (2016) compared the efficacy of alendronate as a means of restricting bone loss in aged female rats, which were sedentary, estrogendeficient, or both.…”
Section: Failure Of Mechanoadaptation With Agingmentioning
confidence: 94%
“…(48) The significant increase in osteoclast number along the SFx was expected at 2 weeks following PTH treatment. (31,49,50) This may be explained by the PTH induction of monocyte chemotactic protein-1, which is responsible for differentiation and recruitment of osteoclast precursors in early remodeling phases. (51,52) The mechanism of the anabolic action of PTH is also supported by other factors, including calcium availability and the calcium sensing receptor.…”
Section: Discussionmentioning
confidence: 99%